1970
DOI: 10.1128/am.20.1.145-150.1970
|View full text |Cite
|
Sign up to set email alerts
|

Biological Uptake of Phosphorus by Activated Sludge

Abstract: The ability of activated sludge to remove phosphates was studied by adding carrier-free 32 P to raw sewage and measuring incorporation of the radioactivity into the cells over a period of time. Radioisotope determinations indicated that 48% of the 32 P radioactivity was removed by 12 hr. However, chemical methods indicated that only 30% of the orthophosphate apparently disappeared from the sewage during this period. Experiments with sludge prelabeled with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1973
1973
2021
2021

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…No release was observed in the final clarifier. A literature search showed that “luxury uptake” of phosphorus occurred in several plants in the USA and India but those were all high‐rate plants with limited or no nitrification (Levin & Sharpiro, 1965; Milbury et al, 1971; Srinath et al, 1959; Vacker et al, 1967; Yall et al, 1970). The author concluded that the release of phosphorus in the second anoxic zone resulted from anaerobic conditions in that zone.…”
mentioning
confidence: 99%
“…No release was observed in the final clarifier. A literature search showed that “luxury uptake” of phosphorus occurred in several plants in the USA and India but those were all high‐rate plants with limited or no nitrification (Levin & Sharpiro, 1965; Milbury et al, 1971; Srinath et al, 1959; Vacker et al, 1967; Yall et al, 1970). The author concluded that the release of phosphorus in the second anoxic zone resulted from anaerobic conditions in that zone.…”
mentioning
confidence: 99%